2011
DOI: 10.1002/lsm.21062
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of sebaceous glands by δ‐aminolevulinic acid‐based photodynamic therapy: An in vivo study

Abstract: Focused damage of sebaceous glands can be achieved with ALA-PDT when low concentrations of ALA (2.5-5.0%) and short incubation times (to 2 hours) were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…18,19 This mechanism could be applied to porphyrins, which are important molecules for PDT photosensitizers. 1,20,21 Electrondonor-connecting cationic porphyrins have been synthesized to examine the activity control during interaction with DNA. 22,23 The OFF → ON activity controls of pyrene 22 -and anthracene 23 -connecting porphyrins by DNA were successfully established.…”
Section: ■ Introductionmentioning
confidence: 99%
“…18,19 This mechanism could be applied to porphyrins, which are important molecules for PDT photosensitizers. 1,20,21 Electrondonor-connecting cationic porphyrins have been synthesized to examine the activity control during interaction with DNA. 22,23 The OFF → ON activity controls of pyrene 22 -and anthracene 23 -connecting porphyrins by DNA were successfully established.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, a recent study has shown that sebaceous glandtargeted accumulation of ALA-PpIX and distinctive damage to sebaceous glands by PDT still can be achieved by shortening the incubation time and decreasing the ALA concentration [27]. All patients tolerated the treatment without application of topical anesthesia and showed no serious side effects such as acneiform eruption, scarring or infection, except for transient erythema, exfoliation, and hyperpigmentation in four of 15 patients.…”
Section: Discussionmentioning
confidence: 86%
“…First, efficacy of continuous application of low‐dose photosensitizers has some scientific validity. One group reported that satisfactory anti‐inflammatory effects around sebaceous glands can be achieved with ALA‐PDT with no prominent damage in the epidermis with low concentrations of ALA (2.5–5.0%) applied in the mouse in vivo . Researchers also recently demonstrated that application of 5% ALA was clinically effective for Asian acne patients without notable side‐effects .…”
Section: Discussionmentioning
confidence: 99%